(untitled) (Fiep Bulletin - online, 2014)
The competitive practice of the golf, as well as in other modalities, it is completely different from the recreational practice. However, a lot of times the typical golfers don’t spend a lot of hours of his/her time for the physical training. The objective of this study was to verify the answers in a golfer’s of high income physiologic indicators by the application of a specific training periodization. It was verified that there was gets better significant in the indicators neuromusculars observed through increases in the acting of the hip flexing in 60 seconds and, mainly, in the hip mobility and trunk observed in the test of seat-and-reaching. Very favorable values were observed in the corporal composition and VO2máx, and in this last one it was also verified stability during the whole periodization. It is concluded verifying that the results suggest the adoption of a similar specific periodization of optimizing the golfers’ of high income acting, based mainly on indicators neuromusculars and of corporal composition.